The Study Examines The Impact of Dividends on The Cash Flows of PT. Central Bank Asia From 2019 to 2023 - Aan Sukanah, Neng; Hernawati, Euis (International Research & Development for Human Beings (IRDH), 2024)
The author uses a quantitative method, specifically SPSS version 29 with the Pearson Product Moment method, to determine the impact of dividends on the cash flow of Central Bank Asia. The results indicate a significant correlation between dividends and cash flows, with a significance level of 0.030 above 0.05. The size of the influence between dividends and cash flows is 83.6%. The T-Test results indicate that Thitung 3,907 surpasses Table 3,182, implying that the independent variable influences the dependent variable, specifically the dividend's impact on the cash flow, thereby validating the author's hypothesis.